Penerapan Media Interaktif untuk Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) pada Siswa Kelas IV Sekolah Dasar - Ghina Naradatul Jannah; Muhaiminah Jalal (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study is motivated by the observation that during the teaching and learning process of Natural and Social Sciences (IPAS), many students still demonstrate low learning motivation. The use of conventional teaching methods, such as lectures and written assignments, tends to be less effective in attracting students' interest. The purpose of this research is to describe the implementation of interactive media in the Natural and Social Sciences (IPAS) subject for fourth-grade students at SD Negeri 02/IX Sekernan and to determine whether the use of interactive media can improve students' learning motivation in this subject. This study employs a classroom action research design, consisting of two cycles. Each cycle includes four stages: planning, implementation, observation, and reflection. Data collection techniques used in this study include observation, interviews, and documentation. The research subjects are fourth-grade students at SD Negeri 02/IX Sekernan. The results of data analysis indicate that the use of interactive media can enhance students' learning motivation in the Natural and Social Sciences (IPAS) subject. Observation results show an increase in student engagement from the first cycle to the second, with the average score rising from 71.27% (categorized as fair) to 81% (categorized as good). It can be concluded that the use of interactive media can improve the learning motivation of fourth-grade students in the Natural and Social Sciences (IPAS) subject at SD Negeri 02/IX Sekernan.